Library security and safety handbook : prevention, policies, and procedures - Shuman, Bruce A. (American Library Association, 1999)
"Bruce A. Shuman, an expert in library security, offers a complete and practical guide to recognizing security risks and preventing problems posed by patrons and staff. He offers practical advice on developing security policies and procedures for staff to follow when confronted with security problems." "By combining practical measures with the reality of serving the public, Shuman discusses how to recognize the motives and unique problems some patrons may pose. He explains how to be vigilant without being paranoid about library security."--Jacket